Calendar anomalies in selected Asian stock markets / Nur Fathiah Mohd Shah - Mohd Shah, Nur Fathiah (Faculty of Business Management, University Teknology MARA, 2018)
Efficient market hypothesis (EMH) states that stock price will fully reflect all the available information in the market. This implies that no investor can create abnormal profit in efficient market. However, there are several markets that do not obey the EMH which to be called, anomalies. Presence or absence of the calendar anomalies may be varied according to its market capitalization. The objective of this study is to examine the presence of day-of-the-week effect and January effect in five selected Asian stock exchanges namely Kuala Lumpur Composite Index (KLCI), Jakarta Stock Exchange (JKSE), Nikkei 225 (N225), Shanghai Stock Exchange (SSE) and Hang Seng Index (HSI) using daily and monthly closing price between 1997 and 2017. This study used dummy variable regression method to analyze the presence of calendar anomalies throughout the period. The findings suggest that there exist day-of-theweek effect and weekend effect in SSE and JKSE. More interestingly, Monday returns are strongly negative in JKSE while SSE shows positive Monday returns. Nevertheless, there is evidence on January effect in JKSE only over the study period. Result from non-parametric test shows that day-of-the-week effect and weekend effects presence in JKSE, SSE and KLCI. Meanwhile there is no evidence for January effects in five selected Asian markets. Results from non-para c test are in line with the dummy variable regression except for KLCI and JKSE. We uggest risk taker investor to invest in short-tenn while risk averse invest in long-term investment.